Critical EFL and critical literacy: the impacts of designing and implementing a cycle of tasks in a public school setting for critical language and critical literacy development - Farias, Priscila Fabiane (2018)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2018.